Mix proportion test and engineering characteristics analysis of loess-based cement slurry material - He, Laping; Ge, Zhonghua; Long, Zhao; Guo, Zhiyuan; Ye, Shuaihua (Frontiers in Materials, 2025)
To address the challenges of limited space, quality control issues, and ensuring stable self-compaction of backfill materials in trench backfilling projects, a loess-based cement slurry was developed as a flowable backfill material by using loess as the primary base material and incorporating an appropriate amount of admixture for solidification and improvement. The permeability, collapsibility, and disintegration of the loess-based cement slurry were analyzed by varying the cement content and curing age. The slump test was first conducted to determine the optimal water content for varying cement contents, aiming for a slump of 180 mm. Subsequently, the compressive strength was tested using an orthogonal experimental design. The analysis revealed the optimal mix ratio for the loess-based cement slurry: 8% naphthalene sulfonate formaldehyde condensate, 3% sodium sulfate, 0.5% sodium thiosulfate, and 0.08% ethylene glycol. Experimental results indicated that with 4% cement content, the loess-based cement slurry exhibited a maximum permeability coefficient of 0.977 × 10−5 and a maximum collapsibility coefficient of 0.865 × 10−2, confirming that both permeability and collapsibility meet the required standards. When the cement content exceeds 6%, the cement paste shows minimal collapse. This study offers an efficient and reliable technical solution for backfilling operations in loess regions.